2016
DOI: 10.1186/s12968-015-0221-2
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical effects of left ventricular midwall fibrosis in non-ischemic cardiomyopathy

Abstract: BackgroundLeft ventricular (LV) mid-wall fibrosis (MWF), which occurs in about a quarter of patients with non-ischemic cardiomyopathy (NICM), is associated with high risk of pump failure. The mid LV wall is the site of circumferential myocardial fibers. We sought to determine the effect of MWF on LV myocardial mechanics.MethodsPatients with NICM (n = 116; age: 62.8 ± 13.2 years; 67 % male) underwent late gadolinium enhancement cardiovascular magnetic resonance (CMR) and were categorized according to the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
75
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 28 publications
(28 reference statements)
6
75
1
Order By: Relevance
“…21 Recent studies have reported that LV twist in patients with systolic heart failure (overall mean LV EF 31%) is reduced within a range of 4.1-6.1 degrees compared with healthy persons. 29- 33 The present result, 4.3±2.0 degrees of LV twist, is consistent with those reports, irrespective of the imaging method.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…21 Recent studies have reported that LV twist in patients with systolic heart failure (overall mean LV EF 31%) is reduced within a range of 4.1-6.1 degrees compared with healthy persons. 29- 33 The present result, 4.3±2.0 degrees of LV twist, is consistent with those reports, irrespective of the imaging method.…”
Section: Discussionsupporting
confidence: 81%
“…In the progression of DCM, mid-myocardial replacement fibrosis disturbs circumferential deformation and twist motion, which results in a "stiffer" LV and leads to deleterious systolic and diastolic ventricular function. 33 This corroborates our finding that LV torsion is more appropriate than longitudinal strain for determining a reduced FC (Figure 3). Furthermore, we demonstrated that LV torsion was strongly associated with the amount of diastolic dysfunction (r=−0.67) in DCM patients.…”
Section: Grantssupporting
confidence: 81%
“…The importance of early diagnosis of Fabry disease and its cardiac manifestations is now well established. Enzyme replacement therapy is more efficient when started early, before the development of irreversible cardiac sequelae, such as fibrosis . Two‐dimensional strain may help provide early detection of Fabry disease among patients with apparent HCM.…”
Section: Discussionmentioning
confidence: 99%
“…Enzyme replacement therapy is more efficient when started early, before the development of irreversible cardiac sequelae, such as fibrosis. [24][25][26] Two-dimensional strain may help provide early detection of Fabry disease among patients with apparent HCM. Furthermore, in patients with known mutations but without LVH, 2D strain screening may allow the identification of preclinical myocardial damage, leading to an earlier institution of enzyme replacement therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, LGE with blood suppression may be achieve my combining either a T2 preparation [9, 11, 13] with IR or by combining a magnetization transfer (MT) preparation with IR [12, 15]. In these schemes, the myocardial signal is reduced relative to the blood signal thereby reducing the inversion times to null the myocardium.…”
Section: Introductionmentioning
confidence: 99%